WORKSHOP PENULISAN PROPOSAL PENELITIAN TINDAKAN KELAS BAGI GURU-GURU DI SEKOLAH ISLAM TERPADU INSAN KAMIL SIDOARJO - Lestariningsih Lestariningsih (STKIP PGRI Sidoarjo, 2018)
Based on the observations that have been done in Insan Kamil Islamic School, it can be known some problems in writing proposal classroom action research faced by teachers. The purpose of this program of dedication is to overcome this problem by conducting an effective and efficient training for teachers in the Insan Kamil Islamic School of Management related to professional management. Development of the competence of teachers in this institution with a training system or workshop will be effective if done with a training system that is guided by the basic principles of management and training stages as follows: 1). The planning stage is based on the training needs assessment, 2). Organizing phase, i.e. preparation of training program, 3). implementation phase of the training program planning and coordination in the implementation stage of the training, and 4). The evaluation phase of training implementation. Based on the results of the presentation that has been submitted by the participants it can be seen that the participants already understand about the meaning and way of making classroom action research proposal. Varied titles of proposals made by participants show that participants have a high level of creativity as well as each participant has a unique problem in undergoing classroom learning activities.